Variances in physiological parameters associated with stress tolerance between seven Brassica oleracea varieties - Davosir, Dino; Šola, Ivana; Ludwig-Müller, Jutta (Frontiers in Plant Science, 2025)
Economically important Brassica oleracea plants are increasingly used as an alternative to the traditionally used Arabidopsis thaliana as models in plant stress biology. However, the extensive diversity of B. oleracea varieties, belonging to different vegetable forms, is often overlooked. Due to previous results indicating that basal levels of stress parameters (reference baseline values in unstressed plants) are important predictors of stress tolerance, we selected seven varieties to comparatively analyze the basal levels of a wide array of stress parameters, intending to guide future studies. A high variability was observed between the varieties for most parameters, including osmolytes, photosynthetic pigments, and antioxidative parameters. Particular interest was given to specialized metabolites, such as phenolics and glucosinolates, with established links between metabolites and the corresponding biosynthesis gene expression levels. Among all varieties tested, cauliflower exhibited the highest levels of phenolic and other antioxidant parameters, suggesting it may be the most resistant to oxidative stress. Meanwhile, kohlrabi, Brussels sprout, and Savoy cabbage excelled in photosynthetic and glucosinolate-related parameters, indicating higher tolerance to stresses affecting photosynthesis and glucosinolate-driven stress responses. Our results set the ground for future stress application studies to deal with the observed B. oleracea variability accordingly. We concluded that no single parameter alone can be used as a reliable indicator of stress tolerance. Therefore, we recommend that future studies employ a broad range of parameters and varieties to evaluate responses to specific stresses with B. oleracea varieties as promising alternative plant models.